The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.2c09667
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Parylene-C Laser-Induced Graphene Electrodes for Microsupercapacitor Applications

Abstract: Laser irradiation of polymeric materials has drawn great attention as a fast, simple, and cost-effective method for the formation of porous graphene films that can be subsequently fabricated into low-cost and flexible electronic and energy-storage devices. In this work, we report a systematic study of the formation of laser-induced graphene (LIG) with sheet resistances as low as 9.4 Ω/sq on parylene-C ultrathin membranes under a CO2 infrared laser. Raman analysis proved the formation of the multilayered graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Parylene C is a superior barrier layer that protects from moisture, corrosion, and airborne contaminants. 24 Applied as a vapor, the coating layer perfectly conforms to complex shapes and provides complete and even coverage. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Parylene C is a superior barrier layer that protects from moisture, corrosion, and airborne contaminants. 24 Applied as a vapor, the coating layer perfectly conforms to complex shapes and provides complete and even coverage. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated proof-of-concept electrodes for electrochemical sensors, strain sensors, and in-plane MSCs by using this method. Correia et al 74 studied the formation of LIG on ultrathin parylene-C membranes using CO 2 infrared laser irradiation (Figure 5b). Optimizing laser parameters, they achieved LIG formation with low resistance, reaching values as low as 9.4 Ω/sq.…”
Section: Recent P-msc Advancementsmentioning
confidence: 99%
“…(b) Schematic of assembling Parylene-C film LIG-MSC electrodes created with laser-writing. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Recent P-msc Advancementsmentioning
confidence: 99%
“…Figure 2(C) displays the SEM images of the PI sheets, which seem to have a low porous carbon structure. Increasing porosity is directly linked to gas release during laser graphitization [20]. Higher laser power means more gas is released from the photothermal conversion, resulting in larger pore distribution and undesirably higher porosity in flexible sensors.…”
Section: Characterization Of Carbonized Idesmentioning
confidence: 99%